(untitled) (Eurasian Journal of Ecology, 2021)
The article presents the analysis results of the spectrum and frequency of distribution of the fetus chromosomal set of 590 pregnant women living in the city of Aktobe and various districts of the Aktobe region in Kazakhstan. Biological material was obtained by biopsy of the chorion and placenta, amniocentesis and cordocentesis. For the preparation of chromosome formations, the conventional “direct” method and the classical method of cell cultivation were used. Metaphase cells were stained with GTG and FISH methods. In total, 64 (10.9%) cases of fetal karyotype abnormalities were detected. Of these, genomic abnormalities accounted for 59 (10.0%), and structural – 5 (8.5%). Among the genomic abnormalities in 39 (66.1%) cases, the fetus had a Down syndrome karyotype. The frequency of chromosomal abnormalities in the fetus of pregnant women in Aktobe, where industrial facilities of ferrous and nonferrous metallurgy are located, was 7.9%. The frequency of fetal chromosomal abnormalities in 3 districts of Aktobe region (fetal karyotypes of 39 pregnant women were studied) without large industrial facilities was 12.8%, and with the presence of large industrial complexes in 5 districts (fetal karyotypes of 131 pregnant women were studied) – 19,8%, which is 1.5 times more. Thus, it can be assumed that technogenic pollution by large industrial complexes (mining, cement, chemical, oil and gas processing industries) of places of residence contributes to the appearance of genomic and structural disorders of the genetic apparatus of human cells. Key words: prenatal diagnosis, fetal karyotype, chromosomal abnormalities, technogenic factor.